Estrategias didácticas y su influencia en el proceso de aprendizaje en la modalidad virtual de los estudiantes de séptimo año de básica de la Unidad Educativa Darío C. Guevara periodo 2021-2022 - Córdova Yugsi, Lady Tatiana (2022)
This research analyzed the didactic strategies and their influence used in virtual education and their relationship with the learning styles of the students of the Unidad Educative “Darío C. Guevara” of Babahoyo, using a quantitative approach, that is, a study of the variables involved in the problem and a collection of information through techniques such as the survey. For this purpose, 58 teachers were identified as a sample for the case study and were surveyed about the didactic strategies used during the virtual period, in addition, various students were surveyed and tested and information was obtained on their perceptions about the form of virtual education, respectively. The results show that teachers mainly use instructional strategies that focus on individualized instruction and, less frequently, use instructional strategies related to expository skills and collaborative work. Also, the study found that students' learning styles varied, with the majority being centered between divergent, convergent and assimilative styles, a situation that was unknown to teachers. This shows the ways in which students perceive and process information, so teachers should implement didactic strategies based on the facilities provided by virtual tools.